The music of Zumaile village, Zambia - Mensah, Atta Annan (International Library of African Music, 1970)
Zumaile village lies south of Minga Mission in the District of Petauke, Eastern Province of Zambia, within three miles of the Mozambique border. The village people belong to the Nsenga tribe. In 1923 a Roman Catholic Mission was established at Minga, some 20 miles north, and in the following year its evangelizing activities spread to Zumaile where, at the time this survey was made in September 1968, most of the villagers had been converted to Roman Catholicism. Some generations ago Zumaile (according to local tradition) had arrived from the Nsenga tribe in Mozambique and settled on this spot. Many of the musical traditions of the village had become obsolete and new ones had replaced them. What follows is a brief description of these traditions.
Keywords: Nsenga (African people); Ethnomusicology; Music; Zambia; African Music